A giant fibrinoid pericardial mass in a patient with rheumatoid arthritis: a case report. Issue 2 (20th May 2019) - Cañas, Felipe; Lopez Ponce de León, Juan David; Gomez, Juan Esteban; Cañas, Carlos Alberto
Abstract: Background : Rheumatoid arthritis (RA) is a chronic inflammatory disease of the joints, which may extend to extra-articular organs. Extra-articular manifestations have been considered as prognostic features in RA, and pericardial disease is one of the most frequent occurrences. Rheumatoid arthritis pericarditis is usually asymptomatic and is frequently found on echocardiography as pericardial thickening with or without mild effusion. Severe and symptomatic cases are rare, but pericardial masses are even rarer. We report a patient with erosive, nodular seropositive RA, and progressive functional deterioration owing to a giant pericardial mass compressing the right cardiac chambers. Case summary: The patient was a 79-year-old man. Cardiac magnetic resonance imaging revealed a pericardial lesion measuring 10 × 9 × 6 cm with complex structures in its interior, which had compressive effects on the right atrium and right ventricle, severely limiting diastole. Late gadolinium enhancement of the lesion walls and pericardium suggested pericarditis. Surgical resection was performed, and a soft mass with liquid content was extracted. The patient recovered well with improvements in symptoms and the functional status. Histopathological studies ruled out neoplasm, vasculitis, and infection, and the entire mass showed fibrinoid material associated with fibrinoid pericarditis. Discussion: Symptomatic RA pericarditis is a rare cardiac manifestation of RA, whilst associated significant haemodynamic compromise is even rarer. The condition could manifest with a giant compressive pericardial mass composed of fibrinous material, with particular involvement of the right ventricle. Exclusion of other conditions, such as neoplasms and infections, is necessary.